Net Primary Productivity and Productive Structure of Eucalyptus tereticornis Smith Plantations Grown in Gangetic Plain - Singh, R. P. (Indian Forester, 1982)
The present investigation deals with the net primary producitivity of the aboveground and underground parts and the productive structure of five different aged planations of Eucalyptus tereticornis grown in Gangetic plain of India under similar climatic and edaphic conditions. The current annual net production is more than the mean annual net production both aboveground and under ground parts. Aboveground cuarrent annual net production yields significant positive correction (r=0.96) with the photosynthetic biomass while the aboveground mean annual production shows high significant correcation (r=0.94) with biomass. underground and aboveground current annual net production are highly correlated having significant correlation (r=O.98) and have direct bearing with dbh (r=0.99). Productive structure shows the pyramidal shape of organic matter distribution in vertical stratification.